(untitled) (Web of Teachers: Inderscience Research, 2026)
This article examines the teaching of the Russian verb system to native Uzbek speakers using inter-lingual and intra-lingual analogies. A classification of Russian verbs, organized into models, is proposed, along with a system of exercises to facilitate the acquisition of Russian verbs in the practice of teaching Russian as a foreign language, covering linguistic, speech, and communicative aspects at the initial stage of learning.